Relative contribution of modifiable risk factors for incident atrial fibrillation in Hispanics, African Americans and non-Hispanic Whites. (15th January 2019) - Shulman, Eric; Chudow, Jay J.; Essien, Utibe R.; Shanbhag, Anusha; Kargoli, Faraj; Romero, Jorge; Di Biase, Luigi; Fisher, John; Krumerman, Andrew; Ferrick, Kevin J.
Abstract: Background: Contribution of modifiable risk factors for the risk of new onset atrial fibrillation (AF) in minority populations is poorly understood. Our objective was to compare the population attributable risk (PAR) of various risk factors for incident AF between Hispanic, African American and non-Hispanic Whites. Methods: An ECG/EMR database was interrogated for individuals free of AF for development of subsequent AF from 2000 to 2013. Cox regression analysis controlled for age > 65, male gender, body mass index > 40 kg/m 2, systolic blood pressure > 140 mm Hg, diabetes mellitus, heart failure, socioeconomic status less than the first percentile in New York State, and race/ethnicity. PAR was calculated as (prevalence of X) ∗ (HR − 1)/HR, where HR is the hazard ratio, and X is the risk factor. Results: 47, 722 persons free of AF (43% Hispanic, 37% Black and 20% White) were followed for subsequent incident AF. Hypertension in African Americans and Hispanics had a 7.93% and 7.66% greater PAR compared with non-Hispanics Whites. Similar findings existed for the presence of heart failure, with a higher PAR in non-Whites compared to Whites. Conclusion: In conclusion, modifiable risk factors play an important role in the risk of incident AF. Higher PAR estimates in African Americans and Hispanics were observed for elevated systolic blood pressure and heart failure. Identification of these modifiable risk factors for atrial fibrillation in non-White minorities may assist in targeting better prevention therapies and planning from a public health perspective. No funding sources were used for this study. Highlights: Relative contribution of factors for the association of atrial fibrillation (AF) in minority populations is poorly understood 47, 722 individuals were followed for incident AF Hypertension in African Americans and Hispanics had greater population attributable risks compared with non-Hispanics Whites. Similar findings existed for the presence of heart failure, with higher attributable risks in non-Whites compared to Whites